Does a Simple Blood Gas Analysis and the Clinical Impression Predict Trauma-Induced Coagulopathy? - Hilbert-Carius, Peter; Lefering, Rolf; Wrigge, Hermann; Hofmann, Gunther O.; Davis, Jesse; Koch, Renè (Hämostaseologie, 2025)
Objectives Trauma-induced coagulopathy (TIC) is common in severely injured patients and is associated with significant morbidity and mortality.Method The association of two parameters of blood gas analysis (hemoglobin [Hb], base excess [BE]) with standard coagulation tests (SCTs) and rotational thrombelastometry (ROTEM) using the database of the TraumaRegister DGU between 2015 and 2022 was studied. In a stepwise approach, the occurrence of a TIC, the correlations between Hb/BE levels and SCT, as well as ROTEM were calculated respectively. Then we aimed to detect relations between different Hb/BE levels and the occurrence of TIC, using standard clotting studies and/or ROTEM respectively.Results TIC occurred in 17.2% of the 68,996 primarily admitted adult patients with Injury Severity Score ≥9. A high correlation was found between Hb/BE and SCT. With a decrease in Hb and BE, the frequency of TIC increased and at an admission Hb <8 g/dL and BE < −6 mmol/L, >60% of patients presented with TIC. Clinical conditions associated with TIC were Glasgow Coma Scale ≤8, blood pressure ≤90 mmHg on the scene or at hospital admission, prehospital volume >1,000 mL, serious injuries to the head and/or the thorax and/or the abdomen and/or the extremities.Conclusion Almost one-sixth of patients present with a TIC at hospital admission. Blood gas analysis samples showed relevant correlations between Hb/BE levels and SCT. The combined closer inspection of Hb/BE and the clinical presentation of the patient is able to predict TIC in the majority of patients.
Keywords: trauma-induced coagulopathy; ROTEM; blood gas analysis; correlation; trauma registry